Working Method of Column Casting In Residential House Construction Project at Jl. Martimbang No.2 - Rifaldi Adi Saputra; Agung Sakti Meldian; Lutfi Hanafi; Aep Saepuloh (Jurnal Teknik dan Science, 2025)
Column work is one of the important stages in constructing a residential house structure, functioning as the main element supporting the load. In the house construction project at Jalan Martimbang No. 2, South Jakarta, the column implementation method is designed to prioritize the accuracy, strength, and durability of the structure. The stages of work include material preparation, formwork manufacture, assembly and installation of reinforcement, and concrete casting according to the established technical specifications. The entire process is carried out by paying attention to quality standards and work safety procedures, as well as considering the conditions of the surrounding environment. With a systematic approach and the use of quality materials, it is expected that the column structures will be able to support the building optimally and meet the planned lifespan of the building.